Firms as knowledge brokers lessons in pursuing continuous innovation - Hargadon, Andrew B.
A set of firms exist whose output consists solely of innovative solutions to novel problems, and whose long-term success depends on their ability to continuously innovate. These firms act as knowledge brokers, spanning multiple industries to innovate by transferring knowledge from where it is known to where it is not. They are often consultants to clients in a range of markets, hut are also groups within a large organization that serve a range of otherwise independent divisions. Rather than producing breakthroughs in any one technology or dominating any one industry, knowledge brokers rely on an alternative but equally powerful strategy that lends itself to continuous innovation. These firms create new products and processes by combining existing technologies in ways that result in dramatic synergy. This article presents a theory of innovation through knowledge brokering that explains the actions and advantages of such firms, and it considers the lessons these firms can offer to others seeking to innovate.